The role of tidal residual currents in the North Aegean Sea - Ioannis G. Mamoutos; Manos Potiris; Elina Tragou; Vassilis Zervakis (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

Spatiotemporal Patterns and Physical Drivers of Satellite-derived Chlorophyll-a in the Aegean Sea - Anthi Koutsaniti; Manos Potiris; Yannis Androulidakis; Vassilis Zervakis; Elina Tragou (Thalassas: An International Journal of Marine Sciences, 2026)
Chlorophyll-a is widely used as an indicator of phytoplankton biomass and primary productivity in the Aegean Sea, with direct implications for marine ecosystem functioning. However, the connection of its variability to physical drivers in the region remain relatively understudied. This study investigates the interannual variability and long-term trends of sea surface chlorophyll-a in the Aegean Sea over 1998–2022 and their relation to physical forcing mechanisms (Black Sea water inflow, sea surface temperature, mixed layer depth, and wind). Atmospheric and oceanic forcing variables were obtained from reanalysis and satellite products. Seasonal dynamics dominate chlorophyll-a variability, with peak values in winter–early spring under deep mixing and minima in summer when strong stratification prevails. Spatial patterns reveal a pronounced north–south gradient, highlighting the influence of the Black Sea Water inflow. No statistically significant long-term trend was detected at the basin scale, however, statistically significant negative trends were observed during the last decade, after 2010. The analysis separates seasonal and non-seasonal variability, linking intra- and interannual fluctuations to both large-scale physical processes and episodic local events. The variability of the Black Sea Water inflow is reflected in the sea level differences between Bosporus (Black Sea entrance) and Dardanelles (Aegean exit). The inflow variability is directly associated with non-seasonal chlorophyll fluctuations, emphasizing the role of horizontal water exchanges in the fertilization of the Aegean Sea and the regional phytoplankton dynamics.

Corrigendum to “A novel method to assess the dilution of complex mixtures in the marine environment: Application to marine scrubber water effluents” [Mar. Pollut. Bull. (2025) 117956]. - Vassilis Zervakis; Vassilis Kolovoyiannis; Loris Calgaro; Elisa Giubilato; Antonio Marcomini; Aikaterini-Anna Mazioti; Christian Ferrarin; Elisa Majamäki; Manos Potiris; Evangelia Krasakopoulou; Elina Tragou; Jaakko Kukkonen; et al. (Marine Pollution Bulletin, 2025)

Modelling the impact of present and future maritime transport on marine pollution at an environmentally sensitive coastal ecosystem (Saronikos gulf, eastern Mediterranean) - Vassilis Kolovoyiannis; Aikaterini Anna Mazioti; Manos Potiris; Ioannis Mamoutos; Elisa Majamäki; Risto Hänninen; Evangelia Krasakopoulou; Elina Tragou; Vassilis Zervakis; Mikhail Sofiev; Erik Fridell; Jaakko Kukkonen; et al. (Marine Pollution Bulletin, 2025)

A novel method to assess the dilution of complex mixtures in the marine environment: Application to marine scrubber water effluents - Vassilis Zervakis; Vassilis Kolovoyiannis; Loris Calgaro; Elisa Giubilato; Antonio Marcomini; Aikaterini-Anna Mazioti; Christian Ferrarin; Elisa Majamäki; Manos Potiris; Evangelia Krasakopoulou; Elina Tragou; Jaakko Kukkonen; et al. (Marine Pollution Bulletin, 2025)

Dense Water Formation Variability in the Aegean Sea from 1947 to 2023 - Manos Potiris; Ioannis G. Mamoutos; Elina Tragou; Vassilis Zervakis; Dimitris Kassis; Dionysios Ballas (Oceans, 2024)
The formation of dense water in the Aegean Sea is important as it affects the deep circulation and the hydrography of the Eastern Mediterranean Sea. In this study, the variability of dense water formation is investigated in relation to forcing mechanisms from 1947 to 2023 in the subbasins of the Aegean Sea, utilising in situ observations from various sources, which have been analysed in combination with satellite altimetry and reanalyses products. The analysis reveals that the Aegean Sea has been in a state of increased dense water formation since 2017 due to the combination of increased surface buoyancy loss and reduced Black Sea water inflow. Extremely high salinity has been recorded in the intermediate layers of the Aegean Sea since 2019. The anticyclonic circulation of the North Ionian gyre during 2017 and 2018 probably also contributed to the rapid transport of highly saline waters in the intermediate and, through dense water formation, the deep layers of the Aegean Sea in 2019. Until 2022, the dense waters formed during the peak of the Eastern Mediterranean Transient still occupied the bottom layers of some deep subbasins of the North and South Aegean; however, the 29.4 kg m−3 isopycnal in the North Aegean and the 29.3 kg m−3 isopycnal in the Southeastern Aegean have gradually deepened by 800 m, permitting the waters forming in the last ten years in the Aegean Sea to settle at ever greater depths. Temperature controls the density variability of the Cretan intermediate water up to the decadal time scale. Increased data availability since 2010 was sufficient to clarify that intrusions of dense water from the North–Central Aegean Sea contributed to the erosion of the Eastern Mediterranean transitional waters in the South Aegean Sea after 2017, as well as to raising the intermediate water masses of the South Aegean to shallower depths. The erosion of the transitional Mediterranean waters in the South Aegean Sea between 1947 and 1955 and 1973 and 1980 coincided with increased dense water formation in the North–Central Aegean Sea. During the peak of the Eastern Mediterranean Transient, the North Ionian circulation, the Black Sea water inflow, the Atlantic Multidecadal Oscillation, and the surface buoyancy fluxes favoured dense water formation in the Aegean Sea.

Implementation of a Far-Field Water Quality Model for the Simulation of Trace Elements in an Eastern Mediterranean Coastal Embayment Receiving High Anthropogenic Pressure - Aikaterini Anna Mazioti; Vassilis Kolovoyiannis; Evangelia Krasakopoulou; Elina Tragou; Vassilis Zervakis; Georgia Assimakopoulou; Alexandros Athiniotis; Vasiliki Paraskevopoulou; Alexandra Pavlidou; Christina Zeri (Journal of Marine Science and Engineering, 2024)
Water quality modeling is a key element for the support of environmental protection and policymaking. The aim of this work is to describe the application of a far-field water quality model for the simulation of marine pollution occurring from heavy metals (cadmium, lead, nickel, copper, and zinc). The highly stressed marine area of the Saronikos Gulf (Aegean Sea, Eastern Mediterranean) was chosen for investigation. Major pollution sources were identified, loads were estimated, and the model was parameterized to reproduce the local seawater conditions. The distribution of the pollutants between the dissolved and particulate phases was examined. The performance of the model set-up was evaluated using field concentration measurements. The described implementation succeeded in reproducing the observed levels of pollution and therefore can be used as a baseline configuration to examine the cumulative impact of future pollution sources; for example, accidental pollution events.

Dense Water Formation in the North–Central Aegean Sea during Winter 2021–2022 - Manos Potiris; Ioannis G. Mamoutos; Elina Tragou; Vassilis Zervakis; Dimitris Kassis; Dionysios Ballas (Journal of Marine Science and Engineering, 2024)
The evolution and drivers of dense water formation (DWF) in the North–Central Aegean Sea (NCAeg) during winter 2021–2022 are studied using observations from two Argo floats and the output of an operational data-assimilating model. Dense water with σθ>29.1 kgm−3 was produced over most of the NCAeg, except for the northeastern part covered by Black Sea water (BSW), where the maximum surface density was

Status, distribution, and threats of the last surviving fan mussel populations in Greece - ORESTIS PAPADAKIS; IOANNIS MAMOUTOS; ALEXIS RAMFOS; GAETANO CATANESE; EVANGELOS PAPADIMITRIOU; JOHN THEODOROU A.; COSTAS BATARGIAS; CHARIKLEIA PAPAIOANNOU; MARIA KAMILARI; ELINA TRAGOU; VASSILIS ZERVAKIS; STELIOS KATSANEVAKIS (Mediterranean Marine Science, 2023)
Since the first confirmed records of mass mortality events (MME) in the Aegean Sea in 2018, Pinna nobilis populations in Greek seas have been decimated. To bolster recovery efforts, this study aimed to assess the status of fan mussel populations in the Aegean and Ionian seas and investigate potential recolonization through natural recruitment. From May 2022 to May 2023, 163 independent underwater visual surveys were conducted across various locations and depths along the Greek coastline. A total of 4348 P. nobilis individuals was recorded, of which 87.3% were found dead and 12.7% were alive. The sole surviving fan mussel populations were located in the semi-enclosed gulfs of Amvrakikos in the Ionian Sea and of Kalloni in the Aegean Sea, with estimated recent mortality rates (excluding potential poaching) of 7.7% and 6.3%, respectively. To track potential new recruitment, a network of larvae collectors was deployed in multiple locations. Additionally, an ocean circulation model (OCM) was developed to predict the export and fate of larvae from the surviving populations in the Marmara Sea towards the Aegean Sea. Beyond the MME, this study identified several other threats, which significantly endanger fan mussel survival. The findings of this study underscore the urgent need to implement protection measures and restoration actions to enhance the chances of P. nobilis survival and recovery in the Greek seas.

Simulating the Interconnected Eastern Mediterranean–Black Sea System on Climatic Timescales: A 30-Year Realistic Hindcast - Stamatios Petalas; Elina Tragou; Ioannis G. Mamoutos; Vassilis Zervakis (Journal of Marine Science and Engineering, 2022)
Inter-basin water exchanges can be quite important in climatic-scale numerical studies simulating the circulation and hydrographic characteristics of neighboring oceanic basins connected through narrow straits. The crucial role of the interaction between the Mediterranean and the Black Seas is often overseen in simulations, which rely mostly on parameterizations to describe the exchange, essentially decoupling the two basins. In this study, the fully interconnected Eastern Mediterranean–Black Sea system is simulated for the historical period (1985–2015) using realistic boundary conditions (lateral, atmospheric and hydrological), with a hydrodynamic fully three-dimensional ocean modeling system. The setup of such a configuration is thoroughly described and the performance of the 30-year hindcast product is validated exhaustively against observations and model results, by evaluating the representation of surface fields, circulation, three-dimensional hydrographic characteristics, volumetric water exchanges, and the spatio-temporal variability of the above. The comparison shows exceptional performance, minimal drift, and substantial improvement compared to modeling studies that do not include the interaction. Moreover, due to the free-run configuration of the simulation (i.e., absence of assimilation schemes) no additional input is required other than the respective boundary conditions, making it possible to reliably extend the same setup for scenarios where observational data are not available, such as in future projections.

The Hellenic Marine Observing, Forecasting and Technology System—An Integrated Infrastructure for Marine Research - Evi Bourma; Leonidas Perivoliotis; George Petihakis; Gerasimos Korres; Constantin Frangoulis; Dionysios Ballas; Vassilis Zervakis; Elina Tragou; Petros Katsafados; Christos Spyrou; Manos Dassenakis; Serafim Poulos; et al. (Journal of Marine Science and Engineering, 2022)
Research infrastructures have been established throughout Europe in order to create robust organizations that will facilitate and enhance research and innovation processes and will advance society with innovative products and services. The Hellenic Integrated Marine Observing, Forecasting and Technology System (component of HIMIOFoTS RI) has been implemented in the framework of the National Roadmap for Research Infrastructures to form a large-scale infrastructure for the marine environment in Greece. It links together ocean observing and forecasting systems, coastal zone monitoring and management practices, as well as ocean engineering testing facilities. The overarching framework of the system supports the coordination of five organizations with expertise in the field of marine science and technology, the central management of research activities, and the common development of services and products. It comprises facilities and resources while it provides open access to research communities (academia, industry) to support the scientific advancements and innovation in their fields. The Hellenic Marine Observing, Forecasting and Technology System was further enhanced during its implementation through significant upgrades and developments in order to extend its observing capacity and the forecasting and technological abilities, while advancing the provided services and products.

A High-Resolution Numerical Model of the North Aegean Sea Aimed at Climatological Studies - Ioannis G. Mamoutos; Emmanuel Potiris; Elina Tragou; Vassilis Zervakis; Stamatios Petalas (Journal of Marine Science and Engineering, 2021)
A new, high-resolution model for the northern part of the Aegean Sea, aimed primarily at climatological research (relaxation and data assimilation-free climate simulations), is hereby presented, along with the results of a 28-year-long simulation covering the period from 1986 to 2013. The model applied is the Regional Ocean Modelling System (ROMS). A significant improvement over previous models of the Aegean introduced in this work is the replacement of parameterizations of the Dardanelles exchange by a fully three-dimensional simulation of the flow in the Strait. The incorporation of part of the Marmara Sea in the model domain enables the interaction with other regional climate simulations, thus allowing climatic variability of the exchange of the Mediterranean and Black Seas. An extensive validation is carried out comparing the model output with all the available observations from several different platforms, i.e., satellite sea surface temperature and height, T/S profiles from R/V ships, and HF radar surface currents velocity. We focus on the model’s ability to reproduce, to some extent, the distinct thermohaline features and circulation patterns that characterize this specific area of the Mediterranean Sea. Our findings, after comparing simulation results with all the available observations, revealed the model’s sufficiency to simulate very adequately the complex hydrology of the North Aegean Sea, and the model’s ability to reproduce incidents of deep-water formation that took place in the region in previous decades during the Eastern Mediterranean Transient (EMT).

Investigation of the Inherent Variability of the Mediterranean Sea Under Contrasting Extreme Climatic Conditions - Angeliki Sampatakaki; Vassilis Zervakis; Ioannis Mamoutos; Elina Tragou; Alexandra Gogou; Maria Triantaphyllou; Nikolaos Skliris (Frontiers in Marine Science, 2021)
The internal variability of the thermohaline circulation of the Mediterranean Sea is examined under contrasting extreme thermal and mass atmospheric forcing conditions. Three millennium-long numerical simulation experiments were performed under: (a) the current climatology, (b) a strong buoyancy forcing (SBF) scenario due to cold and dry conditions resembling the Younger Dryas event, and (c) a weak buoyancy forcing (WBF) scenario due to S1a sapropel deposition-like conditions (warm and wet). To isolate the inherent variability of the system, independent of interannual atmospheric forcing variability, the latter was defined as a perpetual year pertinent to each experiment. Self-diagnosed heat and salt fluxes, consistent to sea-surface characteristics of the above periods, forced three millenium-long, relaxation-free numerical experiments. These simulations were preceded by initial spin-up periods. The inherent spatiotemporal variability of the Mediterranean Sea was analyzed using the empirical orthogonal function (EOF) and spectral analysis on the simulated density fields. Our results revealed that the Mediterranean Sea exhibits high sensitivity to climatic conditions, allowing its circulation to change from anti-estuarine (for the SBF scenario, leading to a buoyancy loss to the atmosphere) to estuarine (for the WBF scenario, corresponding to a buoyancy gain from the atmosphere). In all three experiments, the interannual and decennial variabilities dominate in upper layers, and the decennial variability dominates in the Gibraltar and Sicily Straits. Under current climatic conditions the first two EOF modes express only 60% of the density variability in the deep layers. This contribution exceeds 90% under more extreme conditions. Moreover, the first EOF modes correspond to a basin-wide in-phase variability of the deep layers under the reference and WBF conditions. During SBF conditions the first modes reveal a vertical buoyancy exchange between upper and deeper layers. The second EOF mode of deep waters under both extreme scenarios showed that the western and eastern basins exchange buoyancy in decennial (for the cold/dry) and interdecennial (for the warm/humid) timescales. The residence time of the Eastern Mediterranean deep water was diagnosed to be centennial, semicentennial, and intercentennial for the cases of current period, SBF, and WBF, respectively.

Climate change effects on the marine characteristics of the Aegean and Ionian Seas - Christos Makris; Panagiota Galiatsatou; Konstantia Tolika; Christina Anagnostopoulou; Katerina Kombiadou; Panayotis Prinos; Kondylia Velikou; Zacharias Kapelonis; Elina Tragou; Yannis Androulidakis; Gerasimos Athanassoulis; Christos Vagenas; et al. (Ocean Dynamics, 2016)